1998
DOI: 10.1136/emj.15.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of anaphylaxis in the emergency department.

Abstract: An algorithm for the emergency treatment of anaphylaxis is presented. The need for early hands-on involvement of senior personnel is stressed. Continuous assessment, monitoring of response to treatment, and a low threshold for hospital admission for observation and further treatment if necessary are required. (7 Accid Emerg Med 1998;15:96-98)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 9 publications
0
24
0
6
Order By: Relevance
“…Fall in systolic blood pressure of more than 20 mm Hg and tachycardia are features of moderate anaphylaxis and should be treated with 10 ml/kg colloid intravenous fl uid. If severe cardiovascular collapse occurs, higher volumes (20 ml/kg) should be infused [27].…”
Section: Acute Anaphylaxis Episode Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Fall in systolic blood pressure of more than 20 mm Hg and tachycardia are features of moderate anaphylaxis and should be treated with 10 ml/kg colloid intravenous fl uid. If severe cardiovascular collapse occurs, higher volumes (20 ml/kg) should be infused [27].…”
Section: Acute Anaphylaxis Episode Managementmentioning
confidence: 99%
“…In patients with cardiac arrest or severe hypotension unresponsive to intramuscular doses of epinephrine, intravenous (i.v.) application is an option [2,10,18,27]. Also, it was observed that the subcutaneous (s.c.) administration of adrenaline leads to prolonged but variable absorption related to local vasoconstrictor action and this potential for variability is clearly unacceptable in the critically compromised or shocked patients [14].…”
Section: Adenalinementioning
confidence: 99%
See 3 more Smart Citations